2012
DOI: 10.1245/s10434-012-2657-z
|View full text |Cite
|
Sign up to set email alerts
|

The rs6983267 SNP Is Associated with MYC Transcription Efficiency, Which Promotes Progression and Worsens Prognosis of Colorectal Cancer

Abstract: The presence of the minor allele of rs6983267 at 8q24.21 worsened the prognosis of CRC through up-regulation of MYC transcription. Furthermore, progression of CRC may require global CNA in the presence of the major allele and with lack of MYC transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…In addition, in CRC patients with GG (but not TT) genotype, CCAT2 shows significant association with MYC expression levels, suggesting that the SNP status may also affect CCAT2 function as an RNA transcript. Although most of the previous studies failed to identify a correlation between this SNP and MYC expression, recent research found higher MYC expression in CRC samples containing GG alleles, probably due to the improved purity of the cancer tissues owing to the use of laser microdissection (Takatsuno et al 2012). Our findings on SNP-induced differential CCAT2 expression and function, together with the DNA enhancer element (Pomerantz et al 2009;Tuupanen et al 2009), provide an explanation on the cancer risk conferred by the rs6983267 risk allele (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, in CRC patients with GG (but not TT) genotype, CCAT2 shows significant association with MYC expression levels, suggesting that the SNP status may also affect CCAT2 function as an RNA transcript. Although most of the previous studies failed to identify a correlation between this SNP and MYC expression, recent research found higher MYC expression in CRC samples containing GG alleles, probably due to the improved purity of the cancer tissues owing to the use of laser microdissection (Takatsuno et al 2012). Our findings on SNP-induced differential CCAT2 expression and function, together with the DNA enhancer element (Pomerantz et al 2009;Tuupanen et al 2009), provide an explanation on the cancer risk conferred by the rs6983267 risk allele (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…3f). Some reports have suggested that BubR1 is directly activated by MYC thorough inhibiting the anaphase-promoting complex [9,30]. Together, these results indicate that BubR1 is an important factor in CRC cases carrying the heterozygous GT allele of rs6983267 to promote cancer progression thorough MYC activation.…”
Section: Discussionmentioning
confidence: 55%
“…The GG allele has previously been associated with an increased risk of CRC [8]. Some studies have suggested that CRC patients with rs6983267 GG alleles demonstrate increased vascular invasion and poor survival through the upregulation of MYC transcription factor expression [9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Each selected gene was divided into low and high expression groups at the median point of expression. Additionally, to verify the relevance of our results with GSE17536 database, we used another reference dataset for CRC patients (16). The 91 patients with both CRC stage and DFS time information were selected from this reference dataset and used in validation analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We performed the same prognosis analysis for cancer recurrence with another reference dataset (16) to confirm that this biological behavior is not unique to the GSE17536 database. Also the validation results showed the same tendency that the patients with imbalanced expression of IDH1/2 had a shorter DFS compared to those with balanced expression (Fig.…”
Section: Imbalance Between the Idh1 And Idh2 Expression Is Associatedmentioning
confidence: 99%